2017
DOI: 10.1002/prep.201700095
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Nanocomposites as Burn Rate Catalyst for Composite Solid Propellants

Abstract: In the present study the effect of addition of Al/Fe2O3 based energetic nanocomposites (ENC) to non‐aluminized and aluminized propellants was investigated. Comparative study was carried out using n‐Fe2O3 as burn rate catalyst. Ferric oxide xerogel and Al/Fe2O3 ENC were synthesized by sol‐gel method. The dried xerogel was characterised by Scanning electron microscopy (SEM), Transmission electron microscopy (TEM), X‐ray diffraction (XRD) and X‐ray photoelectron spectroscopy (XPS). TEM and SEM images reveal prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…[4] In general, low decomposition temperature of AP lead to high combustion rate and thrust of composite solid propellants. [5][6][7][8] Therefore, the law of AP decomposition must be studied to improve propellant performance. Transition metals are usually used as AP thermal decomposition catalysts due to their simple preparation, good catalytic performance, and clear catalytic mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…[4] In general, low decomposition temperature of AP lead to high combustion rate and thrust of composite solid propellants. [5][6][7][8] Therefore, the law of AP decomposition must be studied to improve propellant performance. Transition metals are usually used as AP thermal decomposition catalysts due to their simple preparation, good catalytic performance, and clear catalytic mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…The compound analysis of agglomerates carried out using X‐ray diffraction (XRD) PANalytical diffractometer, which is quenched at four pressures viz., 2 MPa, 4 MPa, 6 MPa and 8 MPa, the results are represented in Figure . Based on the absorption effects, the relative intensity (ratio of aluminium peak/alumina peak) of an XRD pattern is directly proportional to the concentration of the component analysis . It can be observed from the Figure , that the alumina content in the agglomerates is consistently increasing with respect to pressure; this is mainly due to the progress in aluminium combustion from the propellant burning surface.…”
Section: Resultsmentioning
confidence: 97%
“…The resultant particle sizes of nano‐aluminium agglomerates is in the range of 1–5 μm, which indicates a higher rate of agglomeration than with micron‐sized aluminium, but these sizes are small relative to the agglomerates of latter . These studies are carried out by maintaining the distance between burning surface and constant quench distance.Hence, most of the studies reported the agglomerated aluminium or its combusted alumina particles whereas the studies on the effect of quenching/collecting distance from the burning surface and accordingly the influence of pressure are very limited, particularly with UFAL particles and the propensity of aluminium agglomerate combustion away from the propellant burning surface requires more advanced studies in order to estimate the agglomerate's fragmentation and combustion characteristics. Incidentally, these features will enable to increase the combustion efficiency and to avoid slag accumulation for further extent.…”
Section: Introductionmentioning
confidence: 99%
“…Gupta et al [21] have made a comprehensive report on various methods available for measurements of the burning rate. Bagalkote et al [22] stated that the enhancement in mean burning rate was observed in composite propellants by adding nano energetic.…”
Section: Introductionmentioning
confidence: 99%